2009
DOI: 10.1002/humu.21015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular karyotyping of patients with unexplained mental retardation by SNP arrays: A multicenter study

Abstract: Genomic microarrays have been implemented in the diagnosis of patients with unexplained mental retardation. This method, although revolutionizing cytogenetics, is still limited to the detection of rare de novo copy number variants (CNVs). Genome-wide single nucleotide polymorphism (SNP) microarrays provide high-resolution genotype as well as CNV information in a single experiment. We hypothesize that the widespread use of these microarray platforms can be exploited to greatly improve our understanding of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 42 publications
(53 reference statements)
1
42
0
Order By: Relevance
“…These should have shown MECP2 duplications in females, and yet no further affected girls have been reported. 16 This contradicts the investigation bias as an explanation for the rarity of those cases. We conclude that MECP2 duplications are a comparatively rare cause of mental retardation in females.…”
Section: Discussionmentioning
confidence: 90%
“…These should have shown MECP2 duplications in females, and yet no further affected girls have been reported. 16 This contradicts the investigation bias as an explanation for the rarity of those cases. We conclude that MECP2 duplications are a comparatively rare cause of mental retardation in females.…”
Section: Discussionmentioning
confidence: 90%
“…Copy numbers were determined using the 2.0 version of the CNAG (Copy Number Analyzer for Affymetrix GeneChip mapping) software package, 21 by comparing SNP probe intensities from patient DNA with those of a sex-matched pooled reference DNA sample (DNA from 10 healthy male individuals). The average resolution of this array platform, described by McMullan et al, 22 is 150-200 kb.…”
Section: Affymetrix Nspi Snp Array Hybridization and Analysismentioning
confidence: 99%
“…2 Several studies reported causative submicroscopic chromosomal aberrations that were only detectable by chromosomal microarray analysis (CMA) 3 and a consensus statement was published that CMA is recommended as first-tier clinical diagnostic test for patients with DD/ID. 4 Besides the detection of submicroscopic deletions and duplications, SNP microarrays can be used for detection of uniparental disomy (UPD).…”
Section: Introductionmentioning
confidence: 99%